2010
DOI: 10.2165/11534470-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Modified-Irinotecan/Fluorouracil/Levoleucovorin Therapy as Ambulatory Treatment for Metastatic Colorectal Cancer

Abstract: Modified-IFL therapy is a practical, effective and tolerable option for ambulatory treatment of advanced colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similarly, the HGCSG focused on the safety of study subjects and decided to reduce the dose to 100 mg/m 2 in this study. Furthermore, the modified IFL regimen (irinotecan, 5-fluorouracil, leucovorin) that was evaluated in a study performed by the HGCSG [14] simultaneously with this study used 100 mg/m 2 irinotecan biweekly, and this dose showed equivalent efficacy to the IFL regimen reported by Saltz et al [15]. Therefore, the dose of irinotecan to be used in this study was set at 100 mg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the HGCSG focused on the safety of study subjects and decided to reduce the dose to 100 mg/m 2 in this study. Furthermore, the modified IFL regimen (irinotecan, 5-fluorouracil, leucovorin) that was evaluated in a study performed by the HGCSG [14] simultaneously with this study used 100 mg/m 2 irinotecan biweekly, and this dose showed equivalent efficacy to the IFL regimen reported by Saltz et al [15]. Therefore, the dose of irinotecan to be used in this study was set at 100 mg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Type I topoisomerase (topo I) induces transient single-stranded breaks of the DNA duplex forming a reversible topo I-DNA covalent complex [24,25]. Stabilization of the cleavable complex brings cells to death and the cleavable complex formed by the human enzyme is the specific target of drugs belonging to the camptothecin family that are in clinical use in colorectal cancer and solid tumors treatment [26][27][28][29][30]. Most eukaryotic type IB topoisomerases are monomeric enzymes including human topoisomerase I, which is comprised of 765 amino acids (91 kDa).…”
Section: Introductionmentioning
confidence: 99%